A comparison of sofosbuvir/velpatasvir and glecaprevir/pibrentasvir for the treatment of hepatitis C infection among people who inject drugs - Shana Yi; David Truong; Brian Conway (Elsevier, 2024)
Background: To eliminate hepatitis C (HCV) infection as a public health concern by 2030, there is a need to develop comprehensive programs among key populations such as people who use drugs (PWUD). Two highly effective regimens are available for initial therapy: glecaprevir/pibrentasvir (G/P) given as 3 tablets/day for 8 weeks and sofosbuvir/velpatasvir (S/V) given as 1 tablet/day for 12 weeks. Data evaluating the safety and efficacy comparing one regimen over another in a population of PWUD is limited. Methods: Patients were identified through outreach events. Viremic patients were offered HCV treatment within a multidisciplinary program. This retrospective comparison analysis focuses on the first 120 sequential individuals who chose either treatment and in whom a definitive outcome of treatment was available between March 1, 2019 and February 29, 2024. The primary outcomes of the analysis were cure of HCV infection and its corelates, as well as safety of the individual regimens. Results: We successfully identified 120 within each of the G/P and S/V treatment groups. Of those on G/P, we note 28.3 % female, 20.9 % Indigenous, 70.8 % using fentanyl, and 51.3 % with unstable housing. Of those on S/V, we note 25.8 % female, 20.8 % Indigenous, and 75 % using fentanyl and 56.7 % with unstable housing. Overall, 118 and 115 patients completed therapy on G/P and S/V, respectively. A total of 118 and 115 completed therapy on G/P and S/V, with virologic relapse documented in 3 and 2 participants on G/P and S/V, respectively. The ITT/mITT cure rates for G/P and S/V were 95.0 %/97.4 % and 94.2 %/98.3 %, respectively. There were 5 drug overdose deaths among those who initiated treatment, one on G/P and 4 on S/V. Conclusion: We have evaluated two highly effective regimens in a group of inner-city PWUD, with comparable success rates well in excess of 90 %. Our data supports the offer of both options for the treatment of PWUD with HCV infection.